Review paperAllergen-specific immunotherapy in atopic dermatitis - Jutel, Marek; Solarewicz-Madejek, Katarzyna; Węgrzyn, Agnieszka (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Allergen-specific immunotherapy (SIT) is the only known causal allergy treatment. Although used for over 100 years, its mechanisms are still the subject of investigation. The safety and efficacy of SIT have been demonstrated in children and adults in many clinical trials, which showed the essential role of SIT in prevention of both new allergy diseases (especially asthma) and new sensitizations. This method is currently recommended in the treatment of IgE-mediated aeroallergens and hymenoptera venom allergy. However, SIT treatment of airborne and food allergy in atopic dermatitis (AD) patients is the subject of investigation. The reported frequency of sensitization to aeroallergens in AD is close to 80% and the clinical significance of avoidance measures has been demonstrated in AD patients. Although initial reports on the efficacy of SIT in AD are somewhat conflicting, new evidence appears to support SIT as a practical and effective method in achieving symptom control in AD. However, new controlled studies including larger patient samples are necessary for further proof of the efficacy of SIT as well as in the development of optimal treatment schedules and preparations for SIT.